2003
DOI: 10.1021/ma034765d
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Morphologies of Confined Copolymer/Nanoparticle Mixtures

Abstract: To isolate the factors that control the structure of nanocomposite thin films, we develop a computational model and scaling theory to investigate the behavior of diblock/nanoparticle mixtures that are confined between two hard walls. We find that in such restricted geometries a polymer-induced depletion attraction drives the particles to these walls. If the particles are chemically distinct from the walls, they will effectively modify the chemical nature of these substrates. This change in chemistry, in turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
124
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 26 publications
4
124
1
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] As an alternate method, besides the in-situ reduction technique, [13][14][15][16] the self-assembly of cadmium selenide, silica, gold and other nanoparticles into two-and three-dimensional ordered structures has been achieved recently, [5][6][7][8][9]11,12,17] led by the theoretical studies of Balazs and coworkers. [18][19][20] Kramer and coworkers [5][6][7][8] used polystyrene ligands to localize gold nanoparticles inside the polystyrene (PS) microdomains of a polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) diblock copolymer, while mixtures of PS and P2VP ligands directed the nanoparticles to the interface between the PS and P2VP microdomains. Bockstaller, et al have shown that the location of particles within the same domain is affected by the size of the nanoparticle.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] As an alternate method, besides the in-situ reduction technique, [13][14][15][16] the self-assembly of cadmium selenide, silica, gold and other nanoparticles into two-and three-dimensional ordered structures has been achieved recently, [5][6][7][8][9]11,12,17] led by the theoretical studies of Balazs and coworkers. [18][19][20] Kramer and coworkers [5][6][7][8] used polystyrene ligands to localize gold nanoparticles inside the polystyrene (PS) microdomains of a polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) diblock copolymer, while mixtures of PS and P2VP ligands directed the nanoparticles to the interface between the PS and P2VP microdomains. Bockstaller, et al have shown that the location of particles within the same domain is affected by the size of the nanoparticle.…”
mentioning
confidence: 99%
“…Our "CH/BD" model integrates a Cahn-Hilliard (CH) theory for binary blends with a Brownian dynamics (BD) simulation for nanoparticles to capture the structural evolution of the mixture (1,8,15). Our "SCF/DFT" combines a self-consistent field theory (SCFT) for diblock copolymers and density functional theory (DFT) for particles to generate the equilibrium morphology of the system (2)(3)(4)(5)7,9,(11)(12)(13)(14). The structural information that we obtained from the CH/BD and SCF/DFT studies was then used to compute the mechanical (1,5,8), electrical (1) or optical properties (2) of the composite.…”
Section: Summary Of the Most Important Resultsmentioning
confidence: 99%
“…Recent theoretical arguments suggest that synergistic interactions between self-organizing particles and a self-assembling matrix material may lead to hierarchically ordered structures. [17][18][19] These predictions were recently confirmed in a study of a diblock copolymer having cylindrical microdomains with added nanoparticles. In this study a co-operative coupled interaction was found that led to hierarchically ordered structures upon thermal-or solvent-annealing where self-orienting, self-assembling arrays of microdomains were found without the use of external fields.…”
mentioning
confidence: 82%